PERENCANAAN STRATEGIS SISTEM INFORMASI KLINIK KECANTIKAN MENGGUNAKAN PENDEKATAN WARD AND PEPPARD (Studi Kasus PT Visi Putri Pramudhita Visi Beauty Clinic) - Monica, Silvi; Wibowo, Arief (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2026)
The development of information technology requires every organization, including beauty clinics, to have an information system that is well-planned, integrated, and aligned with business strategy. This study aims to develop a strategic information system plan for Visi Beauty Clinic using the Ward and Peppard model as the main approach. The model is used to analyze the internal and external business environment, the internal and external IS/IT environment, as well as to formulate IS/IT management strategies. Various analytical techniques are applied, including Value Chain, SWOT, PEST, Five Forces, and the McFarlan Strategic Grid to comprehensively map application needs. The results show that Visi Beauty Clinic faces intense industry competition, increasing customer bargaining power, and demands for technology-based services. On the other hand, the clinic has opportunities to enhance its competitive advantage through service innovation, data integration, and strengthened information systems. Based on these findings, this study proposes an application portfolio that includes an electronic medical record system, health service system, executive information system, supply chain management, financial system, pharmacy application, human resource system, and an integrated distributed database. The resulting IS/IT strategic blueprint provides direction for application development based on strategic, operational, and potential priorities. Overall, the formulated IS/IT strategic plan supports business process efficiency, improves service quality, and strengthens the competitive position of Visi Beauty Clinic in the beauty industry. The implementation of these recommendations is expected to create added value and support the achievement of the company’s long-term vision.